Improving biobehavioral health in younger breast cancer survivors: Pathways to Wellness trial secondary outcomes. (20th September 2022) - Bower, Julienne E; Partridge, Ann H; Wolff, Antonio C; Cole, Steve W; Irwin, Michael R; Thorner, Elissa D; Joffe, Hadine; Petersen, Laura; Crespi, Catherine M; Ganz, Patricia A
Abstract: Background: The Pathways to Wellness trial tested the efficacy of 2 interventions for younger breast cancer survivors: mindful awareness practices (MAPs) and survivorship education (SE). This planned secondary analysis examines intervention effects on stress, positive psychological outcomes, and inflammation (Clincaltrials.gov NCT03025139). Methods: Women diagnosed with breast cancer at or before age 50 years who had completed treatment and had elevated depressive symptoms were randomly assigned to 6 weeks of MAPs, SE, or wait-list control (WLC). Assessments conducted at pre- and postintervention and at 3- and 6-month follow-up measured general stress perceptions, cancer-related intrusive thoughts and worry, positive affect, meaning and peace in life, altruism and empathy, and markers of inflammation. Analyses compared change in outcomes over time in each intervention group relative to WLC using linear mixed models. Results: A total 247 women were randomly assigned to MAPs (n = 85), SE (n = 81), or WLC (n = 81). MAPs statistically significantly decreased intrusive thoughts and worry at postintervention and 3-month follow-up relative to WLC ( P < .027) and statistically significantly increased positive affect and meaning and peace at postintervention, with positive affect persisting at 3-month follow-up ( P < .027). SE statistically significantly decreased intrusive thoughts at 3-month follow-up and statistically significantly increased positive affect at 6-month follow-up relative to WLC ( P < .01). Proinflammatory gene expression increased in WLC relative to MAPs ( P = .016) but did not differ from SE. There were no intervention effects on other outcomes. Conclusion: MAPs had beneficial effects on psychological and immune outcomes in younger breast cancer survivors and is a promising approach for enhancing biobehavioral health.